RhoB regulates cell migration through altered focal adhesion dynamics. Issue 5 (May 2012) - Vega, Francisco M.; Colomba, Audrey; Reymond, Nicolas; Thomas, Mairian; Ridley, Anne J.
Abstract : The Rho GTPase RhoB has been shown to affect cell migration, but how it does this is not clear. Here we show that cells depleted of RhoB by RNAi are rounded and have defects in Rac-mediated spreading and lamellipodium extension, although they have active membrane ruffling around the periphery. Depletion of the exchange factor GEF-H1 induces a similar phenotype. RhoB-depleted cells migrate faster, but less persistently in a chemotactic gradient, and frequently round up during migration. RhoB-depleted cells have similar numbers of focal adhesions to control cells during spreading and migration, but show more diffuse and patchy contact with the substratum. They have lower levels of surface β1 integrin, and β1 integrin activity is reduced in actin-rich protrusions. We propose that RhoB contributes to directional cell migration by regulating β1 integrin surface levels and activity, thereby stabilizing lamellipodial protrusions.